1999
DOI: 10.1029/1999jb900150
|View full text |Cite
|
Sign up to set email alerts
|

A global geoid model with imposed plate velocities and partial layering

Abstract: Abstract. Most inversions of the long-wavelength geoid in conjunction with the seismic tomographic information have so far been carried out under the assumption of either purely whole mantle or perfectly layered circulation. Moreover, modeling the lithosphere as a spherical shell with a uniform low viscosity was found to yield the best fit to the observed geoid. We have tested whether a good prediction of the geoid can also be achieved by including two constraints: a semipermeable behavior of the 660-kin disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
52
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 75 publications
12
52
2
1
Order By: Relevance
“…This implies that mantle viscosity is at least 10 22 -10 26 Pa s. This is consistent with the estimates of the viscosity for the lower mantle, 10 22 -10 24 Pa s [King, 1995;Č adek and Fleitout, 1999;Forte and Mitrovica, 2001]. …”
Section: Viscositysupporting
confidence: 86%
See 1 more Smart Citation
“…This implies that mantle viscosity is at least 10 22 -10 26 Pa s. This is consistent with the estimates of the viscosity for the lower mantle, 10 22 -10 24 Pa s [King, 1995;Č adek and Fleitout, 1999;Forte and Mitrovica, 2001]. …”
Section: Viscositysupporting
confidence: 86%
“…This is only marginally consistent with the observed seismic velocity variations [Weber, 1993;Lay et al, 1997;Liu et al, 1998;Castle et al, 2000]. Other factors such as chemical heterogeneities and anisotropy can be more important for seismic velocity variations.…”
Section: Lateral Temperature Variationsmentioning
confidence: 44%
“…Our analyses of rebound data from formerly glaciated regions (64) and of deglaciation-induced changes in the dynamic flattening and rotation of the Earth (65)(66)(67) are consistent with the highviscosity results, although these solutions are also ice-model dependent. Inversions of geoid and seismic tomographic data are less sensitive to the choice of ice models (the observed geoid needs corrections for the GIA contribution) and point to an increase in depth-averaged mantle viscosity of one to three orders of magnitude from average upper to lower mantle (68)(69)(70)(71)(72)(73). Likewise, inferences of viscosity from the sinking speed of subducted lithosphere also point to high (3-5) × 10 22 Pa s values for the lower-mantle viscosity (74).…”
Section: Discussionmentioning
confidence: 99%
“…We have assumed that the physical conditions at the surface can be approximated by free slip and we have neglected the surface forces which may result from the mineral changes at the boundary between the upper and lower mantle.Čadek and Fleitout [37] have recently demonstrated that the free slip may not be appropriate for the top mantle boundary and that the non-uniqueness of the inversion can be significantly reduced if the observed plate velocities are imposed at the base of the lithosphere. The long-wavelength forces acting at the 660-km discontinuity and hampering the mass exchange between the upper and lower mantle have been discussed by several authors [38,39].…”
Section: Limitations Of Inversionmentioning
confidence: 99%